PEMBUKUAN DAN PELAPORAN INFORMASI AKUNTANSI KEUANGAN BERBASIS PSAK 45: PADA PANTI ASUHAN AL-AMANAH, PALEMBANG - Rita Martini (Politeknik Negeri Sriwijaya, 2018)
This report aims to examine the implementation of non-profit entity financial reporting atPanti Asuhan Al-Amanah, Palembang referring to Pernyataan Standar AkuntansiKeuangan Number 45 (PSAK 45). The data used in this study is the data related to thepreparation of financial statements of financial transactions orphanage. The discussionin this report is how the process of recording transactions, the process of over viewingtransactions, preparing financial statements of activity reports, statements of financialposition, and cash flow statement. Based on the facts obtained, the orphanage has notmade a financial report. Results based on the financial statements made, the orphanagedecreased net assets in the period of December 2017.